2004
DOI: 10.1093/carcin/bgh116
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acids (CLAs) decrease prostate cancer cell proliferation: different molecular mechanisms for cis-9, trans-11 and trans-10, cis-12 isomers

Abstract: The aims of this study were to examine the anti-proliferative effects of different concentrations of a commercial preparation of conjugated linoleic acids (CLA) mixture of isomers [cis-9, trans-11 CLA (c9,t11 CLA): trans-10, cis-12 CLA (50:50)] and their constituent isomers on PC-3, a human prostatic carcinoma cell line, and to study their effects on gene expression (mRNA and protein levels) of different enzymes and oncoproteins involved in oncogenesis and progression of prostate cancer. This includes pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 30 publications
8
88
1
3
Order By: Relevance
“…Importantly, our studies point to a critical role for Bcl-2 in mediating the apoptotic effects of CLA in TM4t cells. Previous Western blot studies indicated that t10,c12-CLA induced either a modest 20-25% loss, or no loss, of total cellular Bcl-2 protein in cultured colon, prostate or breast cancer cells [23,26,27]. However, using mitochondrial fractions, we found that t10,c12-CLA induced a marked concentrationdependent decrease of mitochondrial Bcl-2 after 3 days of treatment (10% of control levels relative to VDAC at 40 μM).…”
Section: Discussioncontrasting
confidence: 51%
“…Importantly, our studies point to a critical role for Bcl-2 in mediating the apoptotic effects of CLA in TM4t cells. Previous Western blot studies indicated that t10,c12-CLA induced either a modest 20-25% loss, or no loss, of total cellular Bcl-2 protein in cultured colon, prostate or breast cancer cells [23,26,27]. However, using mitochondrial fractions, we found that t10,c12-CLA induced a marked concentrationdependent decrease of mitochondrial Bcl-2 after 3 days of treatment (10% of control levels relative to VDAC at 40 μM).…”
Section: Discussioncontrasting
confidence: 51%
“…The common objectives in most studies using addition of FA in the diet, is to decrease saturated and trans FAs and increase conjugated linoleic acid (CLA)s, 18:3n-3, 20:5n-3, and 22:6n-3. These changes in FAs are related to human-health benefits (Ha et al, 1987;Ochoa et al, 2004), changes in the microbial population (Boeckaert et al, 2006), influences on animal metabolism (Bauman et al, 2011) or to enhancement of the overall performance of offspring, when fed to dams during pregnancy and lactation (Pickard et al, 2008;Or-Rashid et al, 2010). There are known differences between the FA profile of meat of grass fed animals and animals fed silage or concentrate-based diets (Poulson et al, 2004;Noci et al, 2005), but there is little information regarding the FA profile of cattle fed tropical grasses.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows a high repeatability value; however, both methods have low repeatability (but similar) values and low correlations for the trans-10,cis-12. This isomer attracts great interest with regards to its potential health effects, which include decreasing proliferation of prostate cancer cells, reducing overall body fat and enhancing body protein [25][26][27], as well as its potential detrimental effects, which include the promotion of colon carcinogenesis and the promotion of atherosclerosis [28,29]. This may be due to the small concentration of the trans-10,cis-12 isomer.…”
Section: Discussionmentioning
confidence: 99%